Synthesis and Antimicrobial Activity of N-Norfloxacin Mannich Bases of Isatin and Its Derivatives - Pandeya, S.N.; Singh, B.N.; Shukla, S.K.; Singh, Meera (Asian Journal of Chemistry, 2010)
Schiff bases of isatin (and derivatives) with isoniazid and their N-norfloxacin Mannich bases were synthesized. Their chemical structures have been confirmed by IR, 1H NMR and by elemental analyses. Antimicrobial evaluation was done against twenty six pathogenic bacteria and six pathogenic fungi. Most of the N-Mannich bases showed higher activity against most of the bacteria in comparison to norfloxacin. All the fungal strains were sensitive to the synthesized N-Mannich bases at the concentration of 50 μg/mL.